Influence of methodologies on learning disabilities in university students (LACCEI, 2024)
The methodological strategies of learning assessment of university students are an ongoing problem that always requires a creative proposal that includes the actors of this process. The main objective of the study is to identify and compare methodologies related to the learning problems of university students. For the methodological process of the research, under a quantitative approach, a non-experimental design was carried out, taking as reference the management of educational institutions in which the difficulties that teachers have in the application of pedagogical methodologies in teaching to improve learning and academic performance of university students are identified. In the results, there is a predominance of both medium and high levels, as IS has a high level with a percentage value of 72.2%, on the other hand, competencies social maintains a high level with a value of 57.6%. On the other hand, for the medium level the E with a value of 96.0%, and finally the methodologies learning problem with a value of 57.6%. In conclusion, it was analyzed the strategies obtained by means of investigations for autonomous learning will allow better performance in the study, having a way the applied methodology where takes to have a margin on the part of the students therefore, when having before the implementation of the active methodology of problem-based learning, it is obtained in a range of low and average after the implementation of this methodology that in turn is demonstrated a significant process for percentages of the strategies of learning in that it is fomented in these investigations.